음악산업의 공간적 분포 연구 -서울시 음악산업 가치사슬을 중심으로 - 홍보영; Bo Yeong Hong; 김경민; Kyung Min Kim (한국경제지리학회지, 2015)
음악산업은 창의산업의 한 영역으로 간주되며 문화적 측면 뿐 아니라 사회경제적으로 그 영향력이 크다. 또한 다른 산업과의 융복합을 통하여 부가가치 창출에 중요한 역할을 한다. 이러한 음악산업은 창의적인 인력과 문화 소비인구가 집중되어 있는 도시에서 주로 나타나고 있기에, 음악산업 전반에 대한 연구와 도시 공간 내의 입지에 대한 연구는 매우 중요하다. 서울시를 대상으로 음악산업 가치사슬 내 각 가치체계별 도시공간내 입지를 GIS와 공간통계기법을 이용하여 분석하였다. 음악산업은 기획, 제작, 유통, 판매, 그리고 음악공연업으로 가치 체계를 정의할 수 있다. 이러한 음악산업 가치사슬은 도시 공간 내에서 클러스터링을 이루며 공간적 자기상관을 보이는데, 가치사슬별로 주요 집적지역은 다르나 강남, 구로, 마포, 종로 일대 지역에 집중적으로 위치한다 Music industry is considered as a creative industry, which tends to locate within a city. However, there is very few paper analysing spatial patterns of music industry in Korea. This study aims to understand music industry’s value chain and its location pattern; whether it is clustered or dispersed. In detail, music industry contains five sub-industry: planning, manufacturing, distribution, sales and performance. Locational pattern of each sub-industry is tested by GIS and hot spot analysis. There are several findings from this research. First, value chain of music industry make clusters and have a spatial autocorrelation. Second, the result shows that music industry makes a hotspot area at Gangnam, Guro, Mapo and Jongro-Junggu.